Generic Utterances as a Form of Communication - Tonyan, Marika (Armenian Folia Anglistika, 2007)
The generic utterances with the pronouns one, you, we possess all the features specific to the communication process. Unlike the generic utterances containing a noun which express generalization about a certain class, the ones containing the pronouns one, you, we involve the participants of the communication or the person who is in the center of the speaker’s attention. These utterances help realize the functions of self-expression of the speaker. Moreover, they establish a link between the speaker and the listener and exert an impact on the listener.